Influences of Wind and Snow on Northern Tree-Line Environments at Churchill, Manitoba, Canada - Scott, Peter A.; Hansell, Roger I.C.; Erickson, William R. (ARCTIC, 1993)
The influences of wind and snow distribution at the tree line near Churchill, Manitoba, were studied. Wind profiles above the snow surface, snow crystal size and quantity were examined during abrasion experiments with white spruce branchlets. For white spruce, the abrasion zone was evidently within 80 cm above the snow surface, and needle removal by abrasion was strongly influenced by branch age. Removal by abrasion of similar-aged needles was highest in new branches and declined with branch age up to 7 or 8 years, and then increased again with older branches. Trees that grew 80 cm in height in 7 or 8 years were successful in passing through the abrasion zone. In forest-tundra environments the matted forms of trees were snow covered early in winter and received little abrasion. Sparsely needled islands of trees were largely covered with snow at the base. More densely needled trees and some trees within woodlands were less exposed to abrasion. The blockage of air flow resulted in high-speed jets, which cleared out snow within a "horseshoe-shaped vortex" around the base of the tree. Both in much of the woodlands and in the open forest, snow abrasion was minimal or non-existent and snow load on the branches (qali), becomes the prevalent stress. During winter, a large proportion of the snowfall was initially blown off the exposed surfaces of Hudson Bay and the coastal tundra regions, into the woodlands, and eventually across the tree line and into the open forest. As the woodlands filled up with snow in mid-winter, the rate of snow accumulation in the forest increased from double to triple the snowfall. Variations in the rate of accumulation occurred with wind speed and direction. .Key words: tree line, wind, snow, white spruce, abrasion L'influence de la distribution du vent et de la neige à la limite forestière, près de Churchill, au Manitoba, constitue le thème de cette recherche. On a étudié le profil éolien au dessus de la surface de la neige, ainsi que la taille et la quantité des cristaux de neige au cours ...